THE RELATIONSHIP BETWEEN CELEBRITY WORSHIP AND BODY IMAGE ADOLESCENT WHO IDOLIZE K-POP - Utami, Rizkia Nur (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2019)
The background of this study is to research the relationship between celebrity worship and body image among student who likes K-pop. Celebrity worship is a phenomenon of individual admission to a celebrity and body image is individual perception of the state ofthe body. The research intends to describe the relationship between celebrity worship and body image adolescents who idolize K-pop at SMP Negeri 45 Bandung. The approach used in this research is a quantitative and correlational method. The participants are 111 adolescents who idolize K-pop, using purposive sampling. Data in this research collected using an instrument of celebrity worship and body image. processing data using the Rasch model in the winstep application. The result of this research signifies the celebrity worship in the moderate category with a percentage of 43,24%, body image in the positive category with a percentage of 56,8%, and there was a quite negatively significant relationship between celebrity worship and body image. The result of this research are recommendations for school counsellors and future researcher.